A recommendation for a budget management information system - Ong, Andrew Jayson T. (Quezon City University of the Philippines Diliman, 2004)
The proposal for Budget Management Information System has its roots in another project called the Budget Management System, which is geared towards the implementation of budgeting as a means of performance evaluation and generation of cost saving opportunities. It was brought about due to the lack of an enabling environment wherein such a system would be able to become part of the regular operations of the various Accounting Departments in the company. The situation requires an integrated approach to the requirements. With the soft side being part of the ongoing project, the hard part or the technology solution will be met by this new project (BMIS). This aspect is a new initiative as it was assumed that the current Accounting practices could support the BMS but actual results have born out the opposite. The proposal that would be generated by this project will be forwarded to the Executive Vice President where high level discussions between him and the proponent is expected to result in adoption of at least part of the proposal. Expected beneficiaries include the Accounting Department, Top Management and the Middle Management. This project provides a unique opportunity to introduce the company to the concepts used in technology management especially when it comes to the task of technology acquisition. Such projects were often postponed, just done as after thought or proposed by the consultants hired by the company. This approach provides a sustainable way of generating such initiatives internal to the company.
The strategic objectives that the project will be able to contribute to include the implementation of strategic programs as well as support the company moves to become the lowest cost manufacturer of snack foods. Specific objectives include an assessment of the current technology infrastructure related to the Accounting System as well the development of evaluation criteria for technology acquisitions. The Methodology to be used is the System Development Life Cycle (SDLC). Due to time constraints only the Systems Analysis phase will be within the scope of the course. Nonetheless, the proponent will continue the project outside of the course. Research will be largely Internet based with interviews and product demos being the primary mode of data collection.The project is expected to deliver 3 major outputs : the Recommendation proposal itself containing the possible technology solution to the current situation, the project documentation outlining the steps that were done and the technology acquisition templates which will be used for other technology acquisition activities in the future. Assumptions and risks include the possibility that there would be limited solutions available due to the current ruling by the BIR on computerized accounting systems as well as the increased risk of information leaks and data manipulation. The work plan includes 5 major phases that only the first 2 will be the scope of the course Planning-May 2003, Systems Analysis-June-September 2003, Systems Design-Septembe 2003, Systems Development-October-January 2004, Systems Implementation-February-October 2004. The planning phase was able to deliver the Feasibility study containing a list of possible solutions and a cost and benefit analysis. The system analysis phase was able to gather an overview of the existing system and details of the proposed budgeting system. The Recommendation proposal outlines the required changes in the existing Accounting system to meet the requirements of budget management.
In partial fulfillment of the requirements in TM 299.2
Thesis
Keywords: Information technology; Information resources management; Budget management